Confrontation of scabrous expressing and non-expressing cells is essential for normal ommatidial spacing in the Drosophila eye. - Ellis, M.C.; Weber, U.; Wiersdorff, V.; Mlodzik, M. (Development, 1994)
The establishment of neural precursor cells in Drosophila depends on cell-cell interactions and lateral inhibition. Scabrous (sca) is involved in this process by preventing an excess of cells from adopting a neural precursor fate. Specifically in eye development, Sca protein function has been implicated in the spacing pattern that is essential for the ordered appearance of the ommatidial array. During this process sca expression is restricted to neurogenic groups of cells and later to the neural precursors. We report that ectopic sca expression in the morphogenetic furrow results in a rough eye phenotype with oversized and fused ommatidia. These defects in adult eyes are due to the generation of too many ommatidial preclusters in the morphogenetic furrow. Strikingly, sca loss-of-function mutants have an almost identical phenotype. Our results suggest that Sca plays a positive role in establishing the spacing pattern within the furrow and that the quantitative difference in sca expression between neighboring groups of cells is a determining factor in this process. Ectopic expression of Sca also represses endogenous sca expression in the furrow, suggesting that Sca is involved in a feedback loop affecting its own transcription. Interestingly, sca shares homology to a group of extracellular matrix proteins that have been implicated in neuronal differentiation. We present a model for sca function based on its phenotypic and molecular features.